Modeling of Structural Human Dynamic Simulation of Speed Control for Synchronous Reluctance Motor Based on Tuning Cascaded PID Controller with PSO Algorithm (University of Thi-Qar Journal for Engineering Sciences, 2016)
This paper presents simulation and control of synchronous reluctance motor (SynRM). The motor speed is controlled by using Traditional PID controller that have been used in cascaded form. The Particle Swarm Optimization (PSO) is used to find the optimal parameters of the PID controller. Lead-Lag controller introduce in the cascaded controller as a second stage of control. Space vector pulse width modulation (SVPWM) scheme proposed to control the motor by using variable input voltage. A comparison between the manually tuned and PSO tuned cascade controller shows that the PSO give amazing control characteristics for the motor speed and have advantage over the manually tuning controller